Design and analysis of a gearless, direct grid, permanent magnet induction wind generator - Potgieter, Johannes H. J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.